The Influencing Factors on Taxpayer Compliance: A Conceptual Approach - aswar, khoirul; Ermawati; Risda Saragih, Tresia (Information Management and Business Review, 2020)
Starting from the assumption that the problem of taxpayer compliance is important issues throughout the world, both in developed countries or in developing countries because if the taxpayer does not comply, it will cause the desire to do so acts of avoidance, evasion and tax neglect. this research seeks to find out to what extent taxpayers registered with SAMSAT Bekasi City fulfill Motorized vehicle tax liability. Drawing from institutional theory, this study has six objectives: (i) to find out the application of understanding of regulations taxation of taxpayer compliance, (ii) to determine the application of sanctions tax on taxpayer compliance, (iii) to determine the application of the tax rate to taxpayer compliance, (iv) to determine the effect of the application of preferences risks to taxpayer compliance. Therefore, this research contributes to the development of science knowledge and is expected to apply the theory that has been obtained specifically regarding the influence of understanding of tax regulations, tax sanctions and the tax rate for taxpayer compliance, which is moderated by risk preferences.